The hiring of illegal workers: a case study of construction sector in Kota Kinabalu Sabah / Faizah Ahmad and Nurhain Awang - Ahmad, Faizah; Awang, Nurhain (2016)
Labour shortage in the Malaysian country in construction industry has lead towards the increasing of the foreign workers including the illegal workers since the local people do not want to participate and contribute their energy to work in this sector. The aim of this paper is to study the hiring of illegal workers in the construction sector at area Kota Kinabalu Sabah regarding to the objectives of this study are to analyse the factor of trends that influencing the increasing of the illegal workers in the construction sector, the implications of the increasing trends of illegal workers hiring in construction sector and the effectiveness of regulations implementation affecting increasing trends of hiring illegal workers in the construction sector. The types of sampling method that have been used were the random sampling technique with the total sample of 100 to be selected as the respondent in this survey. The instrument used was the distribution of questionnaires to the public as the respondent that come from different background. After collecting data from the questionnaires which has been answered, the data was analysed using the SPSS whereby the data will be analysed using both descriptive (mean and standard deviation) and inferential statistics (Chi-Square and Spearman's Rank). The findings show that there are relationship between trends (pulling and attracting factor) and implication (positive and negative impact) in the increasing of illegal workers with the same result that there are relationship too trends (pulling and attracting factor) and implementation of regulation since the result of finding shows significant value < 0.05. In conclusion, the trends were associated with the implications and also effectiveness in implementation of regulation.